A fast, miniaturised in-vitro assay developed for quantification of lipase enzyme activity. (1st January 2019) - Menden, Ariane; Hall, Davane; Paris, Daniel; Mathura, Venkatarian; Crawford, Fiona; Mullan, Michael; Crynen, Stefan; Ait-Ghezala, Ghania
Abstract: The discovery of allosteric modulators is a multi-disciplinary approach, which is time- and cost-intensive. High-throughput screening combined with novel computational tools can reduce these factors. Thus, we developed an enzyme activity assay, which can be included in the drug discovery work-flow subsequent to the in-silico library screening. While the in-silico screening yields in the identification of potential allosteric modulators, the developed in-vitro assay allows for the characterisation of them. Candida rugosa lipase (CRL), a glyceride hydrolysing enzyme, has been selected for the pilot development. The assay conditions were adjusted to CRL's properties including pH, temperature and substrate specificity for two different substrates. The optimised assay conditions were validated and were used to characterise Tropolone, which was identified as an allosteric modulator. In conclusion, the assay is a reliable, reproducible, and robust tool, which can be streamlined with in-silico screening and incorporated in an automated high-throughput screening workflow.